Deterministic Lateral Displacement: The Next-Generation CAR T-Cell Processing?. (August 2018) - Campos-González, Roberto; Skelley, Alison M.; Gandhi, Khushroo; Inglis, David W.; Sturm, James C.; Civin, Curt I.; Ward, Tony
Reliable cell recovery and expansion are fundamental to the successful scale-up of chimeric antigen receptor (CAR) T cells or any therapeutic cell-manufacturing process. Here, we extend our previous work in whole blood by manufacturing a highly parallel deterministic lateral displacement (DLD) device incorporating diamond microposts and moving into processing, for the first time, apheresis blood products. This study demonstrates key metrics of cell recovery (80%) and platelet depletion (87%), and it shows that DLD T-cell preparations have high conversion to the T-central memory phenotype and expand well in culture, resulting in twofold greater central memory cells compared to Ficoll-Hypaque (Ficoll) and direct magnetic approaches. In addition, all samples processed by DLD converted to a majority T-central memory phenotype and did so with less variation, in stark contrast to Ficoll and direct magnetic prepared samples, which had partial conversion among all donors (<50%). This initial comparison of T-cell function infers that cells prepared via DLD may have a desirable bias, generating significant potential benefits for downstream cell processing. DLD processing provides a path to develop a simple closed system that can be automated while simultaneously addressing multiple steps when there is potential for human error, microbial contamination, and other current technical challenges associated with the manufacture of therapeutic cells.